2021
DOI: 10.1002/rmv.2305
|View full text |Cite
|
Sign up to set email alerts
|

Safety and potency of BIV1‐CovIran inactivated vaccine candidate for SARS‐CoV‐2: A preclinical study

Abstract: Summary The development of effective and safe COVID‐19 vaccines is a major move forward in our global effort to control the SARS‐CoV‐2 pandemic. The aims of this study were (1) to develop an inactivated whole‐virus SARS‐CoV‐2 candidate vaccine named BIV1‐CovIran and (2) to determine the safety and potency of BIV1‐CovIran inactivated vaccine candidate against SARS‐CoV‐2. Infectious virus was isolated from nasopharyngeal swab specimen and propagated in Vero cells with clear cytopathic effects in a bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 60 publications
0
39
0
Order By: Relevance
“…Studies have shown that mice coadministered with a pharmacological inhibitor of elastase and alum-adsorbed SARS-CoV-2 S protein-based vaccines can develop high-affinity serum IgG and IgA antibodies [19], indicating that suppression of neutrophil elastase could improve the efficacy of alum-based injected vaccines. Immunization with the inactivated vaccine candidate BIV1-CovIran formulated with alum adjuvant elicited a high level of SARS-CoV-2-specific neutralizing antibodies in mice, rabbits and nonhuman primates (NHPs) [20]. Immunization with two doses of psoralen-inactivated whole-SARS-CoV-2 vaccine (SARS-CoV-2 PsIV) formulated with alum adjuvant generated dose-dependent neutralizing antibodies and Th2 cell responses in mice [21].…”
Section: Aluminum-based Adjuvantsmentioning
confidence: 99%
“…Studies have shown that mice coadministered with a pharmacological inhibitor of elastase and alum-adsorbed SARS-CoV-2 S protein-based vaccines can develop high-affinity serum IgG and IgA antibodies [19], indicating that suppression of neutrophil elastase could improve the efficacy of alum-based injected vaccines. Immunization with the inactivated vaccine candidate BIV1-CovIran formulated with alum adjuvant elicited a high level of SARS-CoV-2-specific neutralizing antibodies in mice, rabbits and nonhuman primates (NHPs) [20]. Immunization with two doses of psoralen-inactivated whole-SARS-CoV-2 vaccine (SARS-CoV-2 PsIV) formulated with alum adjuvant generated dose-dependent neutralizing antibodies and Th2 cell responses in mice [21].…”
Section: Aluminum-based Adjuvantsmentioning
confidence: 99%
“…Various generic platforms were used to develop the vaccines, such as using viral protein, Adenovirus-vectored vaccines, using an inactivated virus, mRNA, or RNA-based vaccine [184]. [184], [186][187][188][189][190][191][192][193][194][195][196]. aration, more than 983.1 million vaccine doses have been given worldwide [185].…”
Section: Vaccines Against Covid-19mentioning
confidence: 99%
“…Status of COVID-19 Vaccines until 30 November 2021[184],[186][187][188][189][190][191][192][193][194][195][196].…”
mentioning
confidence: 99%
“…The 4 vaccines studied against COVID-19 were [1] the BBIBP-CorV vaccine, which is a monovalent Vero cells vaccine composed of inactivated 19nCoV-CDC-Tan-HB02 (HB02) strain of SARS-CoV-2 virus antigens. [13] ; [2] the ChAdOx1-S/nCoV-19 vaccine, which is a modified rAd vector (ChAdOx1), containing the full-length codon-optimized coding sequence of the spike protein of SARS-CoV-2 (ChAdOx1-S/nCoV-19), with a tissue plasminogen activator leader sequence [14] ; [3] the rAd26-rAd5, which is a recombinant replication-deficient adenovirus (rAd)-based vaccine, containing rAd type 26 (rAd26) and rAd type 5 (rAd5) vectors that both of them carry the gene for SARS-CoV-2 full-length glycoprotein S (rAd26-S and rAd5-S) [2] ; and [4] the BIV1-CovIran (COVIran Barekat), which is an inactivated whole-virus SARS-CoV-2 vaccine [15] . The first two vaccines have been authorized for emergency use by WHO, while the other two vaccines have been listed for emergency use, regionally, so far.…”
Section: -1-study Design Population and Data Repositoriesmentioning
confidence: 99%